Effect of different dietary inclusion levels of whole plant green tomato (Physalis philadelphica) silage on nutrient intake and digestibility, and in vitro rumen fermentation kinetics in sheep - Robles-Jimenez, Lizbeth E.; Narváez-López, Alondra C.; Chay-Canul, Alfonso J.; Sainz-Ramirez, Aurora; Castelan-Ortega, Octavio A.; Zhang, Naifeng; Gonzalez-Ronquillo, Manuel; Vargas-Bello-Pérez, Einar (Frontiers in Veterinary Science, 2022)
This study determined production performance, nutrient intake and digestibility, nitrogen balance and in vitro fermentation kinetics from sheep supplemented with whole plant green tomato (GT) on corn silage (CS) based diets. For 21 days, eighteen Suffolk lambs (38 ± 4 kg of live weight) were grouped into three dietary GT inclusion levels to replace CS: a control diet based on 100% CS (GT0, 570 g /kg DM), while 100 g/kg DM (GT100) and 200 g/kg DM (GT200) of GT were included as replacement for CS. A completely randomized design was used to measure chemical composition, in vivo parameters, in vitro gas production and in vitro rumen fermentation. Compared to GT0, GT100 and GT200 did not affect (P>0.05) DM and OM intake (g/kg LW0.75). Ether extract was higher for GT0 and GT100 (P <0.001) compared to GT200. NDF intake was higher (P<0.05) for GT200 compared with GT0. Intake of lignin was higher (P <0.001) for GT200 than that of GT0 and GT100. Digestibility coefficients for DM, OM, NDF and ADF were lower (P<0.05) in GT100 than the rest of the treatments. Nitrogen intake and nitrogen excreted in faeces and urine was lower (P < 0.001) for GT0. Nitrogen balance was negative for all treatments, being higher for GT200 (P<0.05). Regarding in vitro gas production, "A" (ml/g DM), fermentation rates "B" (h-1) and "C" (h-½), were lower for GT200, while DM disappearance (mg/100mg) was lower for GT100 compared with GT0. Overall, the addition of GT at 100 or 200 g/kg DM in sheep diets negatively affects nutrient digestibility and N balance, so their dietary inclusion is not recommended.